Multi-trait genetic analysis of asthma and eosinophils uncovers pleiotropic loci in East Asians - Lili Zhi; Qiwen Zheng; Yue Jiang; Lu Yu; Linzehao Li; Yingchao Song; Bichen Peng; Chumeng Zhang; Hengxuan Jiang; Ren Li; Frank Mentch; Joseph Glessner; et al. (Nature Communications)
Abstract Asthma is a prevalent respiratory condition with over 100 genetic loci identified through genome-wide association studies (GWAS). However, the genetic basis of asthma in East Asians remains underexplored. To address this, we performed a comprehensive analysis of shared genetic mechanisms between asthma and white blood cell (WBC) traits in East Asians, aiming to identify potential pleiotropic loci. Using linkage disequilibrium score regression (LDSC), we identified a significant genetic correlation between asthma and eosinophil count, further supported by Mendelian randomization (MR) analysis. A multi-trait analysis of GWAS (MTAG) uncovered 52 genome-wide significant loci, including 31 previously unreported loci specific to East Asians. Notably, we discovered a missense variant (rs75326924) in the CD36 gene that exhibits increased expression in lymphocytes and type 2 innate lymphoid cell (ILC2)-enriched cells in asthma patients, confirmed by flow cytometry. Proteomic profiling demonstrated downregulation of immune-related proteins such as Interleukin-7, Oncostatin M, and VEGFA in carriers of rs75326924, a variant previously associated with CD36 deficiency. Our findings provide insights into genetic loci and candidate genes underlying asthma in East Asians, offering potential targets for therapeutic interventions tailored to this population.